Working conditions, quality and perceptions about the practice of medicine: a survey of digestive endoscopists in Argentina - Sanguinetti, José María (2021)
Introduction: The practice of medicine today represents a challenge. Objective: To evaluate the characteristics of the work environment and perceptions about the practice of medicine. Materials and methods: Exploratory and transversal studio, online survey (September to November 2020). The characteristics of the work environment, quality in endoscopy, social networks, conflicts of interest and role of scientific societies were evaluated. Results: 208 professionals. Average age 48.5 years, 66.8 % male. Average age of graduated 23 years; 88.9% (n=185) had a certified specialty and 85.6% were gastroenterologists (n=178). Average workplaces: 2.6; 108 worked less than 40 hours a week (52%), 127 (61%) has management tasks and 63.9% passive guards (n=133). 13.5% (n=28) believe that there are disparities between men and women. 70.2% (n=146) experienced Burnout and 86 (41.3%) experienced or witnessed abuse. Monthly average of procedures 87.6 (5-300). Most perform basic diagnostic and therapeutic studies. 63.4% (n=132) considered the technology with which they work is adequate. 65% (n=136) reuse accessories and 54.8% (n=114) know their adenoma detection rate. 76 physicians (36.5%) use social media to spread the way to disseminate his practice. 28.4% (n=59) recognized conflicts of interest. There is a positive opinion for scientific societies to be involved in the defense of economic interests and a high level of economic dissatisfaction with the profession. Conclusion: This survey provides valuable information to improve training programs. There is a need to improve working conditions and the quality of processes and procedures.